“Dying” or “New Life” of Single-Industry Towns (the Case Study of Socio-economic Adaptation of Residents of Single-industry Settlements in the North-West of Russia) - Elena V. NEDOSEKA; Nikolay I. KARBAINOV (Arctic and North, 2020)
The article is devoted to the socio-economic adaptation of single-industry towns’ population on the example of single-industry settlements in the North-West of Russia. The work’s theoretical and methodological framework is the approaches of scientists who study the grassroots practices of survival of small towns and villages (seasonal work, commuting, a distributed way of life, the informal economy). The empirical base of the study are statistical data collected from the databases of EMISS, SPARK Interfax, the Foundation for the Development of Single-Industry Towns, websites of administrations of single-industry settlements in the Northwestern Federal District, as well as data from field studies collected by the method of semi-formalized interviews with representatives of administrations and deputies of city and regional councils, with ordinary residents of single-industry towns in Republic of Karelia, Leningrad and Vologda oblasts. The study’s preliminary results are presented: first, an analysis of the contradictions in the management approach. Many single-industry settlements in the Northwestern Federal District do not meet the criteria according to which they are included in the official list of single-industry towns. Also, government support measures to rescue “dying” monotowns are ineffective. Secondly, empirical research results show that residents of single-industry towns have developed strategies for adapting to new socio-economic conditions of life, which are not associated with employment in a city-forming enterprise. These strategies include: 1) rotational work or seasonal work; 2) pendulum migration within spontaneous local agglomerations; 3) “distributed lifestyle”; 4) involvement in various spheres of the informal economy. Thus, single-industry towns “do not die” but survive primarily due to the population’s grassroots economic practices.